Simultaneous Coating of Electrospun Nanofibers with Bioactive Molecules for Stem Cell Osteogenesis In Vitro - Mehrdad Zahiri-Toosi; Seyed Jalal Zargar; Ehsan Seyedjafari; Mostafa Saberian; Marziehsadat Ahmadi (Cell Journal, 2024)
Objective: Mesenchymal stem cells (MSCs) are widely recognized as a promising cell type for therapeutic applicationsdue to their ability to secrete and regenerate bioactive molecules. For effective bone healing, it is crucial to select ascaffold that can support, induce, and restore biological function. Evaluating the scaffold should involve assessing MSCsurvival, proliferation, and differentiation. The principal aim of this investigation was to formulate composite nanofibrousscaffolds apt for applications in bone tissue engineering.Materials and Methods: In this experimental study, nanofibrous scaffolds were fabricated using Poly-L-lactic acid(PLLA) polymer. The PLLA fibers’ surface was modified by integrating collagen and hydroxyapatite (HA) nanoparticles.Results: The findings demonstrated that the collagen- and nanohydroxyapatite-modified electrospun PLLA scaffoldpositively influenced the attachment, growth, and osteogenic differentiation of MSCs.Conclusion: Coating the nanofiber scaffold with collagen and nanoparticle HA significantly enhanced the osteogenicdifferentiation of MSCs on electrospun PLLA scaffolds.